Syntheses of fluorooxindole and 2-fluoro-2-arylacetic acid derivatives from diethyl 2-fluoromalonate ester - Harsanyi, Antal; Sandford, Graham; Yufit, Dmitri S.; Howard, Judith A.K. (Beilstein Journal of Organic Chemistry, 2014)
Diethyl 2-fluoromalonate ester is utilised as a building block for the synthesis of 2-fluoro-2-arylacetic acid and fluorooxindole derivatives by a strategy involving nucleophilic aromatic substitution reactions with ortho-fluoronitrobenzene substrates followed by decarboxylation, esterification and reductive cyclisation processes.
Keywords: fluorinated building blocks; fluoroarylacetic acid; fluoromalonate; fluorooxindole; organo-fluorine; selective fluorination

(untitled) - Fried, J.; Sabo, E. F. (J. Am. Chem. Soc., 1954)

(untitled) - Müller, K.; Faeh, C.; Diedrich, F. (Science, 2007)

Fluorine in Medicinal Chemistry and Chemical Biology - Ojima, I. (Wiley-Blackwell, 2009)

(untitled) - Purser, S.; Moore, P. R.; Swallow, S.; Gouverneur, V. (Chem. Soc. Rev., 2008)

(untitled) - Isanbor, C.; O'Hagan, D. (J. Fluorine Chem., 2006)

(untitled) - Kirk, K. L. (J. Fluorine Chem., 2006)

(untitled) - Gribble, G. W. (Chem. Soc. Rev., 1999)

(untitled) - Hall, R. J. (New Phytol., 1972)

(untitled) - O'Hagan, D.; Schaffrath, C.; Cobb, S. L.; Hamilton, J. T. G.; Murphy, C. D. (Nature, 2002)

Houben-Weyl Organofluorine Compounds - Baasner, B.; Hagemann, H.; Tatlow, J. C. (Thieme, 2000)

Fluorine in Organic Chemistry - Chambers, R. D. (Blackwell, 2004)

Organofluorine Chemistry - Uneyama, K. (Blackwell, 2006)

(untitled) - Liang, T.; Neumann, C. N.; Ritter, T. (Angew. Chem., Int. Ed., 2013)

(untitled) - Percy, J. M. (Top. Curr. Chem., 1997)

(untitled) - Seebach, D. (Angew. Chem., Int. Ed. Engl., 1990)

Designing Organic Syntheses: A Progrmmed Introduction to the Synthon Approach - Warren, S. (John Wiley and Sons, 1978)

Organic Synthesis: The Disconnection Approach - Warren, S.; Wyatt, P. (John Wiley and Sons, 2008)

Organic Synthesis: Strategy and Control - Wyatt, P.; Warren, S. (John Wiley and Sons, 2007)

The logic of chemical synthesis - Corey, E. J.; Cheng, X.-M. (John Wiley and Sons, 1995)

(untitled) - Chambers, R. D.; Hutchinson, J.; Thomson, J. (J. Fluorine Chem., 1996)

(untitled) - Chambers, R. D.; Fox, M. A.; Holling, D.; Nakano, T.; Okazoe, T.; Sandford, G. (Chem. Eng. Technol., 2005)

(untitled) - Chambers, R. D.; Hutchinson, J. (J. Fluorine Chem., 1998)

W.O. Patent - Müh, T.; Fiedler, P.; Weintritt, H.; Westerkamp, W.; Reinecke, A. (Method for producing alpha fluoromalonic acid dialkyl esters, 2002)

W.O. Patent - Günther, A.; Weintritt, H.; Böhm, S. (Method for producing a-fluoromalonic acid dialkyl esters, 2005)

W.O. Patent - Braun, M.; Brosch, C. (Production of fluorine compounds, 2002)

(untitled) - Ishikawa, N.; Takaoka, A. (Chem. Lett., 1981)

(untitled) - Ishikawa, N.; Takaoka, A.; Ibrahim, M. K. (J. Fluorine Chem., 1984)

W.O. Patent - Miller, T. A.; Sloman, D. L.; Stanton, M. G.; Wilson, K. J.; Witter, D. J. (Fluorinated arylamide derivatives, 2007)

W.O. Patent - Close, J.; Heidebrecht, R. W.; Kattar, S.; Miller, T. A.; Sloman, D.; Stanton, M. G.; Tempest, P.; Witter, D. J. (Histone deacetylase inhibitors with aryl-pyrazolyl motifs, 2007)

W.O. Patent - Hubbs, J. L.; Mampreian, D. M.; Methot, J. L.; Miller, T. A.; Otte, K. M.; Siliphaivanh, P.; Sloman, D. L.; Stanton, M. G.; Wilson, K. J.; Witter, D. J. (Benzothiophene derivatives, 2006)

W.O. Patent - Bressi, J. C.; Chu, S.; Erickson, P.; Komandla, M.; Kwok, L.; Lawson, J. D.; Stafford, J. A.; Wallace, M. B.; Zhang, Z.; Das, J. (cMET inhibitors, 2010)

W.O. Patent - Leonardi, A.; Riva, C.; Tavecchia, P.; Sironi, G. (Aldosterone receptor antagonists, 2007)

(untitled) - Bergmann, E. D.; Cohen, S.; Shahak, I. (J. Chem. Soc., 1959)

U.S. Patent - Brickner, S. J.; Chen, J. M.; Li, Z. B.; Marfat, A.; Mitton-Fry, M. J.; Plotkin, M. A.; Reilly, U. D.; Subramanyam, C.; Zhang, Z.; Robinson, S. (Substituted heterocyclic derivatives and their pharmaceutical use and compositions, 2008)

(untitled) - Polla, M. O.; Tottie, L.; Nordén, C.; Linschoten, M.; Müsil, D.; Trumpp-Kallmeyer, S.; Aukrust, I. R.; Ringom, R.; Holm, K. H.; Neset, S. M.; Sandberg, M.; Thurmond, J.; et al. (Bioorg. Med. Chem., 2004)

(untitled) - Kim, D.-Y.; Kim, S.-M.; Koh, K.-O.; Mang, J.-Y.; Lee, K.-S. (Bull. Korean Chem. Soc., 2003)

(untitled) - Cho, M.-J.; Cho, M.-G.; Huh, S.-C.; Kim, S.-M.; Lee, K.-s.; Koh, K.-O.; Mang, J.-Y.; Kim, D.-Y. (Bull. Korean Chem. Soc., 2006)

(untitled) - Kang, S.-H.; Kim, D.-Y. (Bull. Korean Chem. Soc., 2009)

(untitled) - Kwon, B. K.; Kim, S. M.; Kim, D. Y. (J. Fluorine Chem., 2009)

(untitled) - Li, H.; Zu, L.; Xie, H.; Wang, W. (Synthesis, 2009)

(untitled) - Sandford, G. (J. Fluorine Chem., 2007)

(untitled) - Chambers, R. D.; Nakano, T.; Parsons, M.; Sandford, G.; Batsanov, A. S.; Howard, J. A. K. (J. Fluorine Chem., 2008)

(untitled) - Chambers, R. D.; Sandford, G.; Trmcic, J.; Okazoe, T. (Org. Process Res. Dev., 2008)

(untitled) - Chambers, R. D.; Nakano, T.; Okazoe, T.; Sandford, G. (J. Fluorine Chem., 2009)

(untitled) - Chambers, R. D.; Fox, M. A.; Holling, D.; Nakano, T.; Okazoe, T.; Sandford, G. (Lab Chip, 2005)

(untitled) - Chambers, R. D.; Fox, M. A.; Holling, D.; Nakano, T.; Okazoe, T.; Sandford, G. (Chem. Eng. Technol., 2005)

(untitled) - Chambers, R. D.; Fox, M. A.; Sandford, G. (Lab Chip, 2005)

(untitled) - Breen, J. R.; Sandford, G.; Yufit, D. S.; Howard, J. A. K.; Fray, J.; Patel, B. (Beilstein J. Org. Chem., 2011)

(untitled) - McPake, C. B.; Sandford, G. (Org. Process Res. Dev., 2012)

(untitled) - Hutchinson, J.; Sandford, G.; Vaughan, J. F. S. (Tetrahedron, 1998)

(untitled) - Beare, N. A.; Hartwig, J. F. (J. Org. Chem., 2002)

(untitled) - Shibata, N.; Suzuki, E.; Asahi, T.; Shiro, M. (J. Am. Chem. Soc., 2001)

(untitled) - Shibata, N.; Ishimaru, T.; Suzuki, E.; Kirk, K. L. (J. Org. Chem., 2003)

(untitled) - Zoute, L.; Audouard, C.; Plaquevent, J.-C.; Cahard, D. (Org. Biomol. Chem., 2003)

(untitled) - Shibata, N.; Kohno, J.; Takai, K.; Ishimaru, T.; Nakamura, S.; Toru, T.; Kanemasa, S. (Angew. Chem., Int. Ed., 2005)

(untitled) - Hamashima, Y.; Suzuki, N.; Takano, H.; Shimura, Y.; Sodeoka, M. (J. Am. Chem. Soc., 2005)

(untitled) - Deng, Q.-H.; Wadepohl, H.; Gade, L. H. (Chem.–Eur. J., 2011)

(untitled) - Li, J.; Cai, Y.; Chen, W.; Liu, X.; Lin, L.; Feng, X. (J. Org. Chem., 2012)

(untitled) - Wu, L.; Falivene, L.; Drinkel, E.; Grant, S.; Linden, A.; Cavallo, L.; Dorta, R. (Angew. Chem., Int. Ed., 2012)

(untitled) - Ishimaru, T.; Shibata, N.; Horikawa, T.; Yasuda, N.; Nakamura, S.; Toru, T.; Shiro, M. (Angew. Chem., Int. Ed., 2008)

(untitled) - Dou, X.; Lu, Y. (Org. Biomol. Chem., 2013)

(untitled) - Hewawasam, P.; Gribkoff, V. K.; Pendri, Y.; Dworetzky, S. I.; Meanwell, N. A.; Martinez, E.; Boissard, C. G.; Post-Munson, D. J.; Trojnacki, J. T.; Yeleswaram, K.; Pajor, L. M.; Knipe, J.; et al. (Bioorg. Med. Chem. Lett., 2002)

(untitled) - Schiefer, I. T.; Abdul-Hay, S.; Wang, H.; Vanni, M.; Qin, Z.; Thatcher, G. R. J. (J. Med. Chem., 2011)

(untitled) - Zhang, F.; Song, J. Z. (Tetrahedron Lett., 2006)

(untitled) - Rozen, S.; Hagooly, A.; Harduf, R. (J. Org. Chem., 2001)

(untitled) - Davis, F. A.; Han, W.; Murphy, C. K. (J. Org. Chem., 1996)

(untitled) - Cantrell, G. L.; Filler, R. (J. Fluorine Chem., 1985)

(untitled) - Bresciani, S.; O’Hagan, D. (Tetrahedron Lett., 2010)

(untitled) - Watanabe, S.; Fujita, T.; Sakamoto, M.; Endo, H.; Kitazume, T. (J. Fluorine Chem., 1990)

(untitled) - Kim, K.-Y.; Kim, B. C.; Lee, H. B.; Shin, H. (J. Org. Chem., 2008)

(untitled) - Yin, J.; Zarkowsky, D. S.; Thomas, D. W.; Zhao, M. M.; Huffman, M. A. (Org. Lett., 2004)